Killer‐Cell Immunoglobulin‐Like Receptors (KIR) and HLA‐Class I Heavy Chains in Ankylosing Spondylitis. (November 2014) - Cauli, Alberto; Piga, Matteo; Dessole, Grazia; Porru, Giovanni; Floris, Alberto; Vacca, Alessandra; Desogus, Elisabetta; La Nasa, Giorgio; Mathieu, Alessandro
Abstract: Postmarketing Phase IV HLA‐B27 (B27) interactions with the killer‐cell immunoglobulin‐like receptors (KIR) have been implicated in the pathogenesis of ankylosing spondylitis (AS), with consistent differences among populations. KIR3DL1 and possibly KIR3DS1 interact with classical B27, whereas KIR3DL2 binds B27 heavy chain dimers. The aim of this review is to summarize data from recent studies performed in our laboratory and from the literature, which provide support for a possible role of KIR3DL2/B27 dimer interactions in the pathogenesis of AS. Recent studies in cells from AS patients and from health controls carrying the predisposing B*2705 and the nonpredisposing B*2709 haplotypes, have shown a higher percentage of positive cells and a higher surface expression of KIR3DL2 receptors on natural killer (NK) and CD4+ T cells in B*2705 AS patients compared with B*2705, B*2709 and B27‐negative healthy controls. Increased expression of HC10‐reactive molecules on AS monocytes was seen, supporting the possible role of the KIR3DL2/B272 pair in the pathogenesis of AS. These results underline the importance of NK cells and innate immunity, and of CD4+ T cells in the inflammatory pathogenesis of AS.